2018
DOI: 10.1016/j.colsurfa.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and disappearance of solvent drops on miscible polymer subphases

Abstract: Traditionally, an interface is defined as a boundary between immiscible phases. However, previous work has shown that even when two fluids are completely miscible, they maintain a detectable “effective interface” for long times. Miscible interfaces have been studied in various systems of two fluids with a single boundary between them. However, this work has not extended to the three-phase system of a fluid droplet placed on top of a miscible pool. We show that these three-phase systems obey the same wetting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…(2011) and Stetten et al. (2018 b ). Theoretical investigations revealed that the presence of mucus affects the interface shape and the surfactant distribution during spreading, as well as rupture of the film if van der Waals forces are present (Matar, Craster & Warner 2002).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2011) and Stetten et al. (2018 b ). Theoretical investigations revealed that the presence of mucus affects the interface shape and the surfactant distribution during spreading, as well as rupture of the film if van der Waals forces are present (Matar, Craster & Warner 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The airway surface consists of a layer of mucin on top of a layer of cilia and tethered macromolecules, whose properties can be described using a viscoelastic model (Stetten et al 2018a). The first experimental investigations in this area are due to Koch et al (2011) and Stetten et al (2018b). Theoretical investigations revealed that the presence of mucus affects the interface shape and the surfactant distribution during spreading, as well as rupture of the film if van der Waals forces are present (Matar, Craster & Warner 2002).…”
Section: Introductionmentioning
confidence: 99%